Refractory atopic dermatitis: successful remission with novel new generation emollient consisting of furfuryl palmitate as an adjunct - Pereira, Rickson; Katke, Vaishali (International Journal of Research in Medical Sciences, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin condition requiring personalized treatment approaches. Conventional therapies, including topical corticosteroids and immunosuppressants, often fail to provide long-term relief, leading to disease relapse and poor quality of life. Recent advancements in JAK inhibitors, along with novel skin barrier-enhancing strategies such as antioxidant-rich emollients, offer new therapeutic possibilities. A 14-year-old female with treatment-resistant AD and a 27-year-old female with AD triggered by topical steroid withdrawal both presented with severe, widespread lesions. Previous therapies, including systemic steroids, immunosuppressants, and other JAK inhibitors, failed to provide sustained improvement. Both patients were treated with Abrocitinib 200 mg OD alongside an antioxidant-rich emollient containing furfuryl palmitate, known for its skin barrier-restoring and anti-inflammatory properties. Within a week, both patients experienced complete itch resolution, followed by full skin clearance (IGA 0) over three months, highlighting the potential synergy between targeted JAK inhibition and antioxidant therapy. These cases underscore the effectiveness of Abrocitinib in severe AD and emphasize the crucial role of furfuryl palmitate-based emollients in accelerating skin recovery. By addressing both inflammation and oxidative stress, this combination therapy presents a promising approach for improving long-term treatment outcomes in refractory AD. Further research is warranted to explore its broader dermatological applications.